Labour inspection within a modernized labour administration - Jatobá, Vera (ILO LimaPE, 2002)
Provides background material towards a better understanding of the role of the labour inspection. Addresses the basic content of the institution, starting with the labour administration-inspection relationship and a brief reference to the 1978 (150) ILO convention on labour administration. Focuses on the task of modernizing the labour inspection and addresses some inspection experiences involving forced and child labour.